Factors Affecting the Environmental Awareness of Vietnamese Citizens - Dung, Nguyen Mau; Ninh, Nguyen Thi Hai (International Journal of Membrane Science and Technology, 2023)
This study aims to investigate the environmental awareness of Vietnamese citizens and identify its affecting factors through the survey of a total of 825 households in the North and the South of Vietnam. Descriptive statistics, comparative analysis and linear regression were mainly used to analyze the survey data. The study results show that the respondents’ positive attitudes on environment protection and the high average score on environmental awareness proxy reflected the relatively high environmental awareness of Vietnamese citizens. Gender, education, household income and accessibility to the information on environmental issues were statistically found to be the significant contributing factors to the environmental awareness through both comparative analysis and linear regression model. More dissemination on environmental issues through various means will probably help improve the Vietnamese citizens’ environmental awareness in the future.